IDEOLOGICAL ASPECTS OF REGULATING MIGRATION PROCESSES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The article analyzes the ideological aspects of managing and regulating migration processes in the current conditions of increasing intensity and scale of global migration. The positive and negative aspects of migration, its ideological impact on receiving and exporting countries, as well as the importance of cultural diversity and dialogue are considered. The need to maintain a balance between humanitarian principles, national interests and security issues in managing migration is justified.